1999
DOI: 10.1210/jcem.84.10.6064
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Dependent Association of a Genetic Polymorphism of Cholesteryl Ester Transfer Protein with High-Density Lipoprotein Cholesterol and Macrovascular Pathology in Type II Diabetic Patients

Abstract: Cholesterol ester transfer protein (CETP) is a key regulating factor of lipid metabolism, and the polymorphism of its gene may be a candidate for modulating the lipid parameters in type 2 diabetic subjects. In a group of 406 type 2 diabetic patients aged 59.5 +/- 10.8 y, with a body mass index of 28.9 +/- 5.3 kg/m2 and HbA1c = 8.2 +/- 1.9%, we studied the B polymorphism at the CETP locus detectable with the restriction enzyme TaqI. Patients were separated into groups, 231 males (78 B1B1, 108 B1B2, 45 B2B2) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
26
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 29 publications
2
26
1
Order By: Relevance
“…In the Framingham cohort, men with the B2 allele had a lower CHD risk (14). In line with these results, it has been observed that male patients with type 2 diabetes and the CETP B2B2 genotype may have a decreased risk for coronary artery disease (CAD) pro-gression (11). Recently, a new polymorphism was described, located at Ϫ629 (A-629C) in the promoter region of the CETP gene.…”
mentioning
confidence: 69%
“…In the Framingham cohort, men with the B2 allele had a lower CHD risk (14). In line with these results, it has been observed that male patients with type 2 diabetes and the CETP B2B2 genotype may have a decreased risk for coronary artery disease (CAD) pro-gression (11). Recently, a new polymorphism was described, located at Ϫ629 (A-629C) in the promoter region of the CETP gene.…”
mentioning
confidence: 69%
“…In support of this hypothesis, several groups have reported associations between mutations at CETP and cardiovascular disease risk itself. 37,38 A few previously published linkage studies have provided only nominal or suggestive evidence that variation in HDL-C is influenced either by a QTL in this region of chromosome 16 or by the 2 candidate loci, CETP or LCAT. A sib-pair linkage analysis of HDL-C concentration data for 30 coronary artery disease families 2 yielded suggestive evidence of linkage (LODϭ2.06), with a QTL linked to D16S313, a marker locus that maps to within 6 cM of the marker loci nearest our multipoint peak.…”
Section: Discussionmentioning
confidence: 99%
“…Progression of atherosclerosis was found to be significantly associated (P Ͻ 0.03) with the B1 allele in a study of 807 Dutch men with CAD (64). French male diabetics are at increased risk of coronaropathies (P ϭ 0.025) with the B1 allele, while there was no effect in females (67). Finns with gall bladder disease have a higher risk of gallstones with the B1 allele (76), and Japanese diabetics have a higher likelihood of microangiopathy (P ϭ 0.009) with the B1 allele (73).…”
Section: Wild-type Proteinmentioning
confidence: 99%